Going horizontal: shifts in funding of global health interventions - Bärnighausen, Till; Bloom, David E.; Humair, Salal (The New England journal of medicine, 2011)
Despite the success of recent vertical (disease-specific) interventions in global health, key organizations have begun to invest in more horizontal approaches for protecting and promoting health. But no single intervention structure is well suited to all contexts.
Gesehen am 25.09.2017